(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Intramuscular hemangiomas are rare benign neoplasms accounting for <1% of all hemangiomas and <20% are found in head and neck area. The muscle most frequently involved is the masseter muscle and very few cases have been reported for the occurrence of these hemangioma in the Sternocleidomastoid, trapezius muscle and scalene anterior muscles. Here, we are presenting a case report of intramuscular hemangioma involving these muscles in a 10-years-old boy. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 203-207